Busca de compostos bioativos de Himatanthus articulatus e Vismia guianensis para o controle de formigas cortadeiras (Atta sexdens): um estudo Biomonitorado - Cruz, Artur da Silva (Universidade Federal de São Carlos, 2026)
Agriculture is one of the most important activities for human subsistence, ensuring the supply of food, fiber, and raw materials. However, its productivity is constantly threatened by several factors, including insect pests. These organisms attack cultivated plants by feeding on leaves, stems, roots, or fruits, which can cause significant losses in both the quality and quantity of agricultural production. Therefore, proper pest management is essential to ensure sustainable harvests and to reduce economic and environmental impacts.Organic compounds from natural products have emerged as promising alternatives in the management of agricultural pests, including leaf-cutting ants, which are among the main insect pests in various crops. These insects cause major damage by cutting leaves and plant parts to cultivate symbiotic fungi, thereby impairing crop development. Unlike synthetic insecticides, plant-derived secondary metabolites such as alkaloids, terpenes, and phenolic compounds exhibit bioactive potential, acting as repellents, toxic attractants, or growth inhibitors. Thus, the study and application of natural compounds represent a sustainable and environmentally safer strategy for controlling these pests.The species Himatanthus articulatus (Apocynaceae) and Vismia guianensis (Hypericaceae) are Amazonian plants of great phytochemical interest due to the diversity of secondary metabolites present in their extracts. H. articulatus, popularly known as “suucuba,” mainly contains iridoids, indole alkaloids, triterpenes, and coumarins, compounds that have been associated with anti-inflammatory, antitumoral, and antiparasitic activities. V. guianensis, traditionally used in folk medicine, is rich in xanthones, anthraquinones, naphthoquinones, and flavonoids, metabolites with recognized antioxidant, antimicrobial, and cytotoxic properties.Using a bioassay-guided (biomonitoring) methodology, it was possible to identify four classes of compounds present in these plants through ethanolic extracts. The species Himatanthus articulatus showed high chemical potential in the study of bioactive compounds against leaf-cutting ants (Atta spp.) and their symbiotic fungus Leucoagaricus gongylophorus. From the crude extract, eight compounds belonging to the class of lactonic iridoids were isolated. Biological assays demonstrated that, at a concentration of 0.1 mg/mL, all iridoids showed significant activity against the symbiotic fungus.In contrast, the extract of Vismia guianensis also showed activity against leaf-cutting ants, enabling the isolation and identification of eight compounds, mainly benzophenones, anthraquinones, and one anthranol. Among these, compound 12 stood out for inducing approximately 60% mortality of the ants within about 10 days of bioassay. Based on this positive biological response, an attempt was made to understand the possible mechanism of action of these metabolites. For this purpose, a homology-based molecular docking approach was employed, suggesting that the activity of the compounds may be related to the inhibition of the enzyme acetylcholinesterase, which is essential for insect neurotransmission.The compounds isolated from Himatanthus articulatus and Vismia guianensis show promising potential for the control of leaf-cutting ants. These results reinforce the importance of natural products as sustainable alternatives to synthetic insecticides.
Search for bioactive compounds from Himatanthus articulatus and Vismia guianensis for the control of leaf-cutter ants (Atta sexdens): a Biomonitored study.
Keywords: Compostos bioativos; Formigas cortadeiras; Atta sexdens; Metabólitos secundários; Vismia guianensis; Himatanthus articulatus; Biomonitoramento; Leafcutter ants; Bioactive compounds; Secondary metabolites; Inseticidas naturais; Biomonitoring; natural insecticides; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ORGANICA::QUIMICA DOS PRODUTOS NATURAIS; 2. Fome Zero e Agricultura Sustentável